2020
DOI: 10.1109/access.2020.3003070
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Image Classification Based on Hard Example Guided CNN

Abstract: The diagnosis of biopsy tissue with hematoxylin and eosin (H&E) stained images has been widely used by pathologists to detect the lesions and assess the malignancy. Nevertheless, the diagnostic result relies on the visual observation of pathologists which may vary from person to person under different circumstances. With the advantage of automatically and adaptively learning features at multiple levels of abstraction, Convolutional Neural Networks (CNNs) have rapidly become promising alternatives for pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…The CNN's immersive design enables the extraction of a collection of distinct characteristics at multiple levels of abstraction without the need for operator intervention [28]. The CNN approach directly relates to the picture used to create the relationship mapping feature [29].…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The CNN's immersive design enables the extraction of a collection of distinct characteristics at multiple levels of abstraction without the need for operator intervention [28]. The CNN approach directly relates to the picture used to create the relationship mapping feature [29].…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Talo [49] demonstrated that pre-trained ResNet [43] and DenseNet [42] to achieve better accuracy than traditional methods in the literature for classifying grayscale and color histopathological images. Similarly, Wang et al [50] proposed a DCNN-based method based on GoogleNet [44] to locate tumors in breast and colon images using complex example-guided training for WSI analysis. Among other DCNN works, Meng et al [29] compared several architectures for classification and segmentation problems on a cervical histopathology dataset.…”
Section: Deep Learning For Computational Pathologymentioning
confidence: 99%
“…Detection of gastric cancer primarily relied on endoscopy images and pathological images. Wang et al [21] developed a Convolutional Neural Network (CNN) model to recognize biopsy tissue from Hematoxylin and Eosin (H&E) stained images and identify diseases. The lesions detected helped assess the malignancy in digestive system-related problems.…”
Section: Literature Reviewmentioning
confidence: 99%